Moderate‐intensity exercise training ameliorates the diabetes‐suppressed spermatogenesis and improves sperm parameters: Insole and simultaneous with insulin. (23rd October 2019) - Samadian, Zahra; Tofighi, Asghar; Razi, Mazdak; Tolouei Azar, Javad; Ghaderi Pakdel, Firouz
Abstract: The current study was conducted to investigate the ameliorative effect of moderate‐intensity exercise training insole and simultaneous with insulin on diabetes (DM)‐induced pathogenesis at the testicular tissue and sperm level. For this purpose, 36 mature male Wistar rats were divided into six groups, including sedentary control (Con), exercise training (EX), sedentary experimental DM‐induced (SDM), exercise training + DM‐induced (DM + EX), insulin‐treated sedentary DM‐induced (DM + INS) and exercise training and insulin‐treated DM‐induced (DM + INS + EX) groups. Following DM induction, the 6‐week exercise training intervention (30 min of moderate‐intensity running on a treadmill, once daily [5 days/week]) was considered in EX groups. The tubular differentiation (TDI) and spermiogenesis (SPI) indices, testicular total antioxidant capacity (TAC), superoxide dismutase (SOD) and glutathione peroxidase (GPX) contents, serum testosterone and insulin levels, the apoptosis ratio and sperm parameters were assessed. The exercise in sole (EX) and simultaneous forms with INS (DM + INS + EX group) ameliorated the DM‐suppressed spermatogenesis and spermiogenesis indices, up‐regulated the serum testosterone and insulin levels, enhanced testicular SOD content, inhibited the apoptosis and improved almost all sperm parameters. In conclusion, exercise training, when simultaneously considered with insulin, fairly boosts the insulin‐induced impacts, including the up‐regulated testicular endocrine and antioxidant status, spermatogenesis and sperm quality.